Prevalence of pulp necrosis cases at the East Selemadeg I Community Health Centre in Tabanan, Bali, from January 2024 to March 2025: Prevalensi kasus nekrosis pulpa di UPTD Puskesmas Selemadeg Timur I Tabanan Bali periode Januari 2024-Maret 2025 - Wijayana, I Nyoman Anugerah Purna; Pratama, I Wayan Agus Wirya; Kusumadewi, Ni Wayan Adi; Palguna, I Gede Pandu (Makassar Dental Journal, 2025)
Untreated caries can lead to pulp tissue death or pulp necrosis. Promotive and preventive measures need to be improved to re-duce the incidence of this condition with the aim of improving the quality of life of the community, especially in the dental and oral health sector. This observational study used a cross-sectional method, showing that the highest number of cases was recorded in October 2024 at 20.5%. Of the total 105 cases, 60% were female patients and 40% were male. This comparison shows that women tend to suffer from pulp necrosis more often, which can be correlated with the tendency for women to snack, causing caries to worsen into pulp necrosis. It is concluded that cases of pulp necrosis at the Selemadeg Timur I Community Health Centre are more common among women, which is related to women's snacking habits that increase the risk of caries.